Transmission of business cycle shocks between the US and the euro area - Gerhard Fenz; Martin Schneider (Oesterreichische Nationalbank (OeNB), 2008)
We analyze the transmission of structural shocks between the US and the euro area within a two-country VAR framework. For that purpose, we simultaneously identify cost-push, demand and monetary policy shocks for both countries using sign restrictions. Our results show that domestic shocks explain the largest share of the forecast error variances for GDP, consumer prices and the interest rate in both countries in the short run, whilst spillovers from the other country and global factors gain importance in the medium run. The strength of the shock transmission between the two countries is quite symmetric. Our approach to the identification of structural shocks allows us to construct confidence bands that account both for estimation and identification uncertainty. We find impulse responses to domestic shocks to be significant while spillovers across countries are insignificant.
Keywords: C32; E37; E40; 330; VAR; shock transmission; sign restrictions; Metropolis-Hastings; confidence intervals; bootstrap